THE EFFECT OF UNDERSTANDING TAX REGULATIONS, UNDERSTANDING TAX ACCOUNTING, AND APPLICATION OF MODERN TAX ADMINISTRATION SYSTEM ON TAXPAYER COMPLIANCE WITH PERSONAL PERSONS WITH TAXATION SANCTIONS AS MODERATING VARIABLES: SURVEY ON INDIVIDUAL TAXPAYERS REGISTERED AT KPP PRATAMA BATAM SELATAN - Afdal, Afdal; Satriawan, Bambang; Robin, Robin; Irfan, Irfan; Khaddafi, Muammar (CV. Radja Publika, 2022)
Taxpayer compliance is a condition where the taxpayer fulfills all tax obligations and exercises tax rights. The purpose of this study is to determine whether there is an effect of understanding tax regulations, understanding tax accounting, and the application of a modern tax administration system on individual taxpayer compliance with tax sanctions as a moderating variable at the South Batam Primary Tax Office. The population in this study amounted to 67,957 individual taxpayers who are required to report taxes. The sampling technique used is simple random sampling and convenience sampling with the sample using the Slovin formula so that the research sample is 100 individual taxpayers. Methods of data collection using a questionnaire. Data were analyzed using Partial Least Square (PLS) with model analysis, namely the measurement model or the outer model and the structural model or the inner model. The results showed that the understanding of tax regulations had a significant positive effect on taxpayer compliance. The path coefficient was 0.208 and the P-Values value was 0.018 <0.05. Understanding tax accounting has a significant positive effect on taxpayer compliance, the path coefficient is 0.624 and the P-Values is 0.000 <0.05. The application of a modern tax administration system has a significant positive effect on taxpayer compliance with a path coefficient of 0.357 and a P-value of 0.000 <0.05. Tax sanctions have a significant negative effect on taxpayer compliance with a path coefficient of -0. 299 and the P-Values value is 0.000 < 0.05. Tax sanctions moderate the relationship between understanding tax regulations and taxpayer compliance. Tax sanctions moderate the relationship between understanding tax accounting and taxpayer compliance. Tax sanctions do not moderate the relationship between the application of the tax administration system to taxpayer compliance.